Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

A randomized phase 1 single-dose polysomnography study of ASP8062, a GABAB receptor positive allosteric modulator - Mark Walzer; Ruishan Wu; Maha Ahmad; Jon Freeman; Gary Zammit; Gerard J. Marek (Psychopharmacology, 2021)
Rationale Previous research suggests that sleep polysomnography and EEG endpoints can be used to assess GABAergic activity; however, the impact of GABA B receptor positive allosteric modulators on sleep endpoints remains unclear. Objectives This phase 1 study compared a single dose of ASP8062 (35 mg or 70 mg), a GABA B receptor positive allosteric modulator, with placebo and paroxetine (40 mg). Methods Healthy adult volunteers were randomized to four treatments (35 mg ASP8062, 70 mg ASP8062, paroxetine 40 mg, or matching placebo), each separated by a 14-day washout. Primary endpoints obtained by polysomnography were time in stage N3 or SWS and time in rapid eye movement (REM) sleep. Secondary endpoints included impact on sleep stages and electroencephalography parameters, pharmacokinetics, nighttime growth hormone (GH), and safety/tolerability. Results In 20 randomized volunteers, ASP8062 led to a significant and seemingly dose-dependent increase in SWS over the entire night; this increase was mainly observed during the first third of the night. ASP8062 did not impact time in REM sleep. Paroxetine had no effect on SWS but produced a significant reduction in time spent in REM sleep. A dose-dependent trend in increased GH release was also observed with ASP8062. Headache and nausea were the most commonly reported treatment-emergent adverse events (TEAEs) for ASP8062; most TEAEs were mild in severity. Conclusions Single-dose ASP8062 (35 and 70 mg) appeared to result in CNS penetration and enhanced GABAergic activity as measured by increases in slow-wave sleep and growth hormone release.

Soil organic carbon stability in forests: Distinct effects of tree species identity and traits - Gerrit Angst; Kevin E. Mueller; David M. Eissenstat; Susan Trumbore; Katherine H. Freeman; Sarah E. Hobbie; Jon Chorover; Jacek Oleksyn; Peter B. Reich; Carsten W. Mueller (Global Change Biology, 2019)
Rising atmospheric CO 2 concentrations have increased interest in the potential for forest ecosystems and soils to act as carbon (C) sinks. While soil organic C contents often vary with tree species identity, little is known about if, and how, tree species influence the stability of C in soil. Using a 40 year old common garden experiment with replicated plots of eleven temperate tree species, we investigated relationships between soil organic matter (SOM) stability in mineral soils and 17 ecological factors (including tree tissue chemistry, magnitude of organic matter inputs to the soil and their turnover, microbial community descriptors, and soil physicochemical properties). We measured five SOM stability indices, including heterotrophic respiration, C in aggregate occluded particulate organic matter (POM) and mineral associated SOM, and bulk SOM δ 15 N and ∆ 14 C. The stability of SOM varied substantially among tree species, and this variability was independent of the amount of organic C in soils. Thus, when considering forest soils as C sinks, the stability of C stocks must be considered in addition to their size. Further, our results suggest tree species regulate soil C stability via the composition of their tissues, especially roots. Stability of SOM appeared to be greater (as indicated by higher δ 15 N and reduced respiration) beneath species with higher concentrations of nitrogen and lower amounts of acid insoluble compounds in their roots, while SOM stability appeared to be lower (as indicated by higher respiration and lower proportions of C in aggregate occluded POM) beneath species with higher tissue calcium contents. The proportion of C in mineral associated SOM and bulk soil ∆ 14 C, though, were negligibly dependent on tree species traits, likely reflecting an insensitivity of some SOM pools to decadal scale shifts in ecological factors. Strategies aiming to increase soil C stocks may thus focus on particulate C pools, which can more easily be manipulated and are most sensitive to climate change.

Looming sounds enhance orientation sensitivity for visual stimuli on the same side as such sounds - Fabrizio Leo; Vincenzo Romei; Elliot Freeman; Elisabetta Ladavas; Jon Driver (Experimental Brain Research, 2011)

Sexual specialization and inbreeding avoidance in the evolution of dioecy - D. Carl Freeman; Jon Lovett Doust; Ali El-Keblawy; Kathleen J. Miglia; E. Durant McArthur (The Botanical Review, 1997)